The Relation of Curanmor News Online Exposure and the Frequency of Curanmor Word of Mouth with the Alertness Level of Students Motorcyclists In Tembalang - Rico Ananda Putra, Yohanes; Pradekso, M.Sc, Drs. Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Curanmor cases that occurred in Tembalang turns out to be phenomenon that also highlighted by college students. There are various curanmor word of mouth broadcast message about students lose motorcycles in various places in Tembalang plus another curanmor news on online mass media very easily accessible. On the other side the increase in the number of cases curanmor occurring in Tembalang shows that in the last few years the alertness level of students motorcyclists on Tembalang decline, where most of the victim are a students. The purpose of this research is to knowing the relation of curanmor news online exposure and the frequency of curanmor word of mouth with the alertness level of students motorcyclists In Tembalang. Theory used in this research is the Cognitive Dissonance Theory by Festinger. The type of this research is explanatory research. This research using non-random dan accidental sample collecting method, with total 30 sample of respondent. Testing instrument used for testing the hypothesis is corelation statistic test. Correlation analysis used in this research is the Pearson correlation analysis. The hypothesis test showed the significant value of Curanmor News Online Exposure variable by 0,880, and 0,499 for the significant value of Frequency of Curanmor Word of Mouth variable. All the significant values are lower than α(0,05), so the both variable are not connected to the Alertness Level of Students Motorcyclists In Tembalang. The conclusion of this research is for college students to aware about persuasive message about curanmor alertness from banner either from the police department or university.